wingless and its signalling pathway have common and separable functions during tracheal development. - Llimargas, M. (Development, 2000)
The Drosophila tracheal tree consists of a tubular network of epithelial branches that constitutes the respiratory system. Groups of tracheal cells migrate towards stereotyped directions while they acquire specific tracheal fates. This work shows that the wingless/WNT signalling pathway is needed within the tracheal cells for the formation of the dorsal trunk and for fusion of the branches. These functions are achieved through the regulation of target genes, such as spalt in the dorsal trunk and escargot in the fusion cells. The pathway also aids tracheal invagination and helps guide the ganglionic branch. Moreover the wingless/WNT pathway displays antagonistic interactions with the DPP (decapentaplegic) pathway, which regulates branching along the dorsoventral axis. Remarkably, the wingless gene itself, acting through its canonical pathway, seems not to be absolutely required for all these tracheal functions. However, the artificial overexpression of wingless in tracheal cells mimics the overexpression of a constitutively activated armadillo protein. The results suggest that another gene product, possibly a WNT, could help to trigger the wingless cascade in the developing tracheae.